Optimizing Employee Performance: The Role of Public Service Motivation and Organizational Citizenship Behavior - Amelia, Emi; Pasca, Yelsha Dwi; Abriyani, Lisdayanti; Hasanah, Ade Sobariah; Pratiwi, Vina Andita; Susnita , Tia Aprilia; Sari, Gita Kartika (Universitas Airlangga, 2024)
Human resource management is a central factor in any organization. Regardless of its form or objectives, an organization is established based on various visions for human interests, and its mission is managed and executed by people. Thus, human resource management focuses on issues related to the workforce. This study examines the impact of Public Service Motivation (PSM) and Organizational Citizenship Behavior (OCB) on employee performance. The respondents of this study were 100 employees from PT Leetex Garment Indonesia. Purposive sampling was used in this study, along with quantitative analysis through multiple regression analysis. The results revealed that PSM and OCB significantly and positively influenced employee performance, with PSM having a t-value of 12.331 and OCB having a t-value of 9.929, surpassing the critical t-value of 1.985. Additionally, the combined effect of PSM and OCB on employee performance was significant, with an F-value of 88.136 and a probability level of 0.000, less than the alpha level of 0.05. This suggests the need for further research into other factors affecting employee performance that were not covered in this study. This finding indicates the usefulness of PSM and OCB in increasing organizational productivity. However, this study also highlights the potential for further investigation into other elements that may influence employee performance, such as leadership style, organizational culture, or managerial support. For practitioners, particularly at PT Leetex Garment Indonesia, these findings might serve as the foundation for developing more effective human resource management strategies.